1996
DOI: 10.1038/hdy.1996.90
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for B chromosome drive suppression in the grasshopper Eyprepocnemis plorans

Abstract: The grasshopper Eyprepocnemis plorans is polymorphic for both a B chromosome and a heterochromatic segment of chromatin on the smallest autosome. Females transmit these to their offspring more frequently after copulating with a male from a population without Bs than after copulating with a male from their own population. Paternity analyses using the heterochromatic segment as a marker showed that the effect of male on female transmission does not depend on fertilization because it occurs even when all the eggs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 29 publications
(18 reference statements)
0
35
0
Order By: Relevance
“…For instance, it has been shown that females get proteinaceous nutrients from male ejaculate, which they incorporate into the eggs they lay, thus increasing their rate of egg production (Pardo et al, 1995). In addition, Herrera et al (1996) reported male effects on female k B . These observations suggest that factors such as the number of matings performed by a female before laying each egg pod or the number of days between mating and laying, could modify female reproductive conditions and change k B from pod to pod.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, it has been shown that females get proteinaceous nutrients from male ejaculate, which they incorporate into the eggs they lay, thus increasing their rate of egg production (Pardo et al, 1995). In addition, Herrera et al (1996) reported male effects on female k B . These observations suggest that factors such as the number of matings performed by a female before laying each egg pod or the number of days between mating and laying, could modify female reproductive conditions and change k B from pod to pod.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining females were crossed to males lacking B chromosomes (low B frequency, or L crosses). Grasshopper culture conditions were similar to those described in Herrera et al (1996).…”
Section: Methodsmentioning
confidence: 99%
“…A mechanism of genetic control in the transmission patterns of these extra elements has been demonstrated in some animals, including the grasshopper Myrmeleotettix maculatus , the mealy bug Pseudococus affinis Brett 1987, 1988), the grasshopper Eyprepocnemis plorans (Herrera et al 1996) and also in some plants including Hypochoeris maculata (Parker et al 1982), Aegilops speltoides (Cebriá et al 1994), and Allium schoenoprassum (Bougourd and Plowman 1996).…”
Section: -1377mentioning
confidence: 99%
“…favouring migration of the marker it carries towards the first polar body. The male effects on transmission ratio of the B2 chromosome through lB females (Herrera et al, 1996) that we have recently observed in E. plorans suggest that meiotic segregation cannot be entirely under female control, thus leaving some scope for sperm effects.…”
Section: Discussionmentioning
confidence: 78%